Synergetic effect of additives on the hardness and adhesion of thin electrodeposited copper films - Mladenović Ivana; Lamovec Jelena; Jović Vesna; Radojević Vesna (Serbian Journal of Electrical Engineering, 2017)
Thin copper films were electrodeposited on a polycrystalline coldrolled copper substrate. The composition of the laboratory-made copper sulphate electrolyte was changed by the addition of various additives. The influence of chloride ion (Cl-), polyethylene glycol (PEG) and 3-mercapto-1-propane sulfonic acid (MPSA) on mechanical and adhesion properties of the electrodeposited copper films was investigated using Vickers microindentation technique. Calculations of the film hardness and adhesion were carried out using composite hardness models of Korsunsky and Chen-Gao. The hardness of the composite system is influenced by the adhesion of the copper film to the substrate. Increasing adhesion corresponds to increasing values of the calculated adhesion parameter b, named the critical reduced depth. When additives are added to a plating solution, the copper deposition mechanism is changed and fine-grained microstructure without the formation of microscopic nodules is obtained. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. TR 32008, Grant no. TR 34011 and Grant no. III 45019]